Особенности состава углеводородов палеозойских нефтей юго-востока Западной Сибири; Нефтехимия; Т. 54, № 6 - Чиркова Д. Ю. Диана Юрьевна; Красноярова Н. А. Наталья Алексеевна; Серебренникова О. В. Ольга Викторовна; Ву Ван Хай (2014, 2014)
Заглавие с экрана